1916
DOI: 10.3181/00379727-14-41
|View full text |Cite
|
Sign up to set email alerts
|

The absorption of phenolsulphonephthalein from the subarachnoid space in diseases of the central nervous system

Abstract: Since 1842 various observers, beginning with Magendie, have demonstrated that pigments injected into the subarachnoid space eventually appear in the urine. Dandy and Blackfan1 were the first to apply this knowledge to the study of pathologic conditions. They showed that phenolsulphonephthalein injected into the subarachnoid space is harmless and appears in the urine in normal infants in from four to ten minutes. Their studies were confined to hydrocephalus in infants and to certain animal experiments. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1974
1974

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In all four animals, more than 90%o of the 14C was penicillin. Similarly, 5 [3H]inulin (0.1 juCi) was spotted directly as purchased from the company. In all cases more than 98% of the 'H activity was at the origin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all four animals, more than 90%o of the 14C was penicillin. Similarly, 5 [3H]inulin (0.1 juCi) was spotted directly as purchased from the company. In all cases more than 98% of the 'H activity was at the origin.…”
Section: Methodsmentioning
confidence: 99%
“…However, Harter and Petersdorf (2) suggested that another factor, viz., an inhibition of efflux from CSF to blood in meningitis, might affect drug distribution. Thlis perceptive insight was based on an analysis of phenolsulphonphthalein (PSP) transport from the CSF in meningitis in humans (5). Subsequently, the active transport of PSP (6) and other substances such as penicillin (7)(8)(9) from the CSF was documented.…”
Section: Introductionmentioning
confidence: 99%